Factors affecting biocompatibility and biodegradation of magnesium based alloys. (2022) - Kumar, Sunil; Katyal, Puneet
Abstract: Magnesium (Mg) as a trace element of human body possesses excellent properties to be a biodegradable medical implant. It has elastic modulus and density almost equal to human bone, excellent biocompatibility and osseointegration; also it shows negligible toxicity in body fluids. Corrosion and mechanical characteristics of Mg and its alloys could be increased by optimized alloying, with reasonable biocompatibility. Surface coatings enhance the surface characteristics of Mg alloys and reduce the degradation rate. In this review the effects of alloying and surface coatings of Mg alloys are summarized on account of the corrosion behaviour, degradation rate and biocompatibility. The combination of alloying and surface coating could be an excellent option for biomedical implants because alloying tackle the hydrogen evolution, corrosion problems and enhance biocompatibility; then coating helps to control the degradation rate of Mg alloys as a result reduces the loss of mechanical properties.